Stunting Management with Exclusive Breastfeeding, Early Breastfeeding Initiation Toddlers at Sei Panas Community Health Center - Roza, Nelli (International Journal of Multidisciplinary Approach Research and Science, 2023)
Indonesia continues to struggle with nutritional issues, which seriously affect the caliber of human resources (HR). The prevalence of stunting in children under the age of five is one of the nutritional issues that is currently of great concern. The goal is to analyze the reduction in stunting by promoting exclusive breastfeeding and Early Breastfeeding Initiation in toddlers. A case control study with 33 mothers of stunted toddlers and 33 mothers of non-stunted toddlers was done in the working area of the Sei Panas health center. Non-probability sampling is used for sampling, while the chi square test is used for data analysis. It was discovered that 18 (78.3%) of the 25 toddlers who did not get only breast milk stunted, with a p-value of 0.003 0.05; OR 4,286 (Lower 1,246 - Upper 14,735). meaning that the incidence of stunting and exclusive breastfeeding have a substantial link. In addition, 15 (65.2%) of the 22 children who did not initiate early breastfeeding had stunted growth, with a v-palue of 0.039 0.05; OR 8,229 (Lower 2,175- Upper 31,132). This indicates that the incidence of stunting and early breastfeeding initiation are significantly correlated. The following interventions are included in the framework for specific nutritional intervention activities typically carried out in the health sector and are aimed at breastfeeding mothers and children aged 0–6 months: 1) Encouraging early initiation of breastfeeding (giving breast milk/colostrum); Public health centers are advised to increase education about exclusive breastfeeding for babies 0–6 months in order to reduce the incidence of stunting in their working area.